2017
DOI: 10.1371/journal.pone.0175688
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-associated acute kidney injury: A cross-sectional study from a single center in China

Abstract: ObjectiveThe objective of this study was to investigate the current situation of vancomycin (VAN)-associated acute kidney injury (VA-AKI) in China and identify the risk factors for VA-AKI, as well as to comprehensively examine the risk related to concurrent drug use. Further, we assessed the outcomes of patients who developed VA-AKI and the risk factors for these outcomes. Finally, we aimed to provide suggestions for improving the prevention and treatment of VA-AKI in China.MethodsWe conducted a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…The selection of diuretics in patients receiving VAN may be an important consideration. The effect of administering Chinese patent drugs concomitantly with VAN on the development of VI‐AKI was demonstrated in a study in a Chinese adult population . The present study was the first to explore the influence of Chinese patent drugs on VI‐AKI in elderly Chinese patients being treated with VAN.…”
Section: Discussionmentioning
confidence: 65%
“…The selection of diuretics in patients receiving VAN may be an important consideration. The effect of administering Chinese patent drugs concomitantly with VAN on the development of VI‐AKI was demonstrated in a study in a Chinese adult population . The present study was the first to explore the influence of Chinese patent drugs on VI‐AKI in elderly Chinese patients being treated with VAN.…”
Section: Discussionmentioning
confidence: 65%
“…Potential risk factors for VCM-induced AKI were extracted based on the following parameters that could be evaluated on the day of initial VCM administration [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]: BMI, CCr, underlying heart disease, type of infection of infective endocarditis, and concomitant medications (non-steroidal anti-inflammatory drugs (NSAIDs), furosemide, aminoglycosides, AMPH-B, TAZ/PIPC, vasopressor drugs, nitric acid-based medicines, and tacrolimus). Vasopressor drugs included etilefrine, noradrenaline, olprinone, milrinone, dopamine, and dobutamine.…”
Section: Methodsmentioning
confidence: 99%
“…To prevent a deteriorated prognosis, early detection of nephrotoxicity is crucial for patients treated with VCM [ 6 ]. Risk factors associated with VCM-induced nephrotoxicity have been reported in several studies, and clinicians and pharmacists should pay attention to patients with these risk factors [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although alternative drugs with relatively less nephrotoxicity are available, vancomycin, due to its effectiveness and low cost, is still the preferred and widely used drug for the treatment of MRSA. According to a multicenter study which included 103 hospitals in China, there were 357,225 cases of vancomycin prescription in the year of 2017 [26], and the incidence of VI-AKI was 16.2%-30.8% [9,27,28]. Although it has been reported that vancomycin TDM facility is available in most academic hospitals in big cities, 76.5% of the patients in these hospitals had inadequate TDM [29].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Yet adverse drug reactions, especially vancomycin-induced acute kidney injury (VI-AKI) are still common [5][6][7][8][9], which signi cantly increase the mortality and medical expenses [10]. Our previous study showed that there was a signi cant insu ciency in the determination of serum creatinine (SCr) and the therapeutic drug monitoring (TDM) in those who were treated with vancomycin [9]. Moreover, in recent years, the minimum inhibitory concentration (MIC) of vancomycin has increased and vancomycin-resistant MRSA has appeared [11,12], which lead to a rise in vancomycin dosage and an increased risk for developing nephrotoxic AKI.…”
Section: Introductionmentioning
confidence: 99%